ILS – INSTRUMENT LANDING SYSTEM GROUND-BASED INSTRUMENT APPROACH SYSTEM (Perner's Contacts, 2009)
The article focuses on ILS – Instrument Landing System with emphasis on its use in air travel. Part of the article focuses on general characteristic and function of ILS system in air travel.